Some considerations on the use of space sound absorbers with next-generation materials reflecting COVID situations in Japan: additional sound absorption for post-pandemic challenges in indoor acoustic environments. Issue 2 (18th November 2020) - Sakagami, Kimihiro; Okuzono, Takeshi
Abstract : In this study, we first point out the possible acoustic problems associated with the post-pandemic operation of built environments. In particular, we focus on the problem of acoustic deficiency due to the lack of absorption. This deficiency, which is likely to be encountered in most enclosed spaces in a range of establishments, is due to the reduced number of audience members or users of the space as a result of social distancing. As one of the promising solutions to this problem, we introduce a sound absorption technique using three-dimensional (3D) space sound absorbers developed through our recent research projects. Significantly, the type of sound absorber proposed herein is made of materials that are especially suited to hygiene considerations. The materials are microperforated panels (MPPs) and permeable membranes (PMs), both of which are easily washable and sanitised. Furthermore, we point out that 3D-MPP or PM space absorbers possess the additional value of aesthetic designability.